Bistability of the cytokine-immune cell network in a cancer microenvironment. (28th April 2017) - Li, Xuefei; Levine, Herbert
Abstract: The immune system features the interaction of many cell types via multiple chemical pathways. Not surprisingly, such a complex system might exhibit multistability, which means that multiple operating states might be allowed under the same external conditions, the actual state being determined by system history. In the context of cancer immunotherapy, understanding how signals from the cancer cells might bias the immune system to emphasize certain of these states might help inform therapeutic strategies. Here, we propose a series of coarse-grained models of the immune system in order to explore the mechanisms that lead to bistability between immune-promoting and immune-suppressing states. We discuss in detail using this modeling framework to help interpret existing experimental data and to predict outcomes for various perturbations to some of the interacting components.